Development of a pseudo/anonymised primary care research database: Proof-of-concept study. (June 2016) - MacRury, Sandra; Finlayson, Jim; Hussey-Wilson, Susan; Holden, Samantha
General practice records present a comprehensive source of data that could form a variety of anonymised or pseudonymised research databases to aid identification of potential research participants regardless of location. A proof-of-concept study was undertaken to extract data from general practice systems in 15 practices across the region to form pseudo and anonymised research data sets. Two feasibility studies and a disease surveillance study compared numbers of potential study participants and accuracy of disease prevalence, respectively. There was a marked reduction in screening time and increase in numbers of potential study participants identified with the research repository compared with conventional methods. Accurate disease prevalence was established and enhanced with the addition of selective text mining. This study confirms the potential for development of national anonymised research database from general practice records in addition to improving data collection for local or national audits and epidemiological projects.